2014
DOI: 10.1364/oe.22.024959
|View full text |Cite
|
Sign up to set email alerts
|

Extracting depth information of 3-dimensional structures from a single-view X-ray Fourier-transform hologram

Abstract: Extracting depth information of 3-dimensional structures from a single-view X-ray Fourier-transform hologramGeilhufe, J.; Tieg, C.; Pfau, Bastian; Guenther, C. M.; Guehrs, E.; Schaffert, S.; Eisebitt, Stefan General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…As a result the tomograms have a higher quality than tomograms recorded with a single axis of rotation. In contrast to obtaining 3D information via a single, high numerical aperture hologram [4] this tomographic approach allows for an isotropic spatial resolution in 3D-with the exception of sample spatial frequencies falling into the missing data pyramid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result the tomograms have a higher quality than tomograms recorded with a single axis of rotation. In contrast to obtaining 3D information via a single, high numerical aperture hologram [4] this tomographic approach allows for an isotropic spatial resolution in 3D-with the exception of sample spatial frequencies falling into the missing data pyramid.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that the depth information could be extracted from a single x-ray hologram using the opaque mask-design. This was achieved by the propagation of the reconstructed complex wave-field through different planes of the sample [4]. In contrast to tomography, the lateral and longitudinal resolution differ from each other by an order of magnitude and the objects to be imaged must be separated laterally from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The reconstruction of the real-space image was obtained via a 2D Fourier transform of the hologram and free-wave propagation along the optical axis to the thin film sample plane. 18,19 In the second test, utilizing absorption contrast rather than XMCD, a gecko-shaped test pattern was deposited on a crystalline MgO(100) substrate using electron-beam induced Pt deposition from organic precursor molecules. Due to the deposition process, the approximately 50 nm thick test object is estimated to consist of only 20-50 at.% Pt, with the remainder being carbon from the precursor molecules.…”
Section: -3mentioning
confidence: 99%
“…Using holography for soft X-ray imaging, first demonstrated in a lensless setup in 2004 [1], is a rather novel approach that is still under heavy development and significant improvements have been made in the past few years [2][3][4][5][6][7][8][9][10][11][12]. Still, permanent holography end stations with user support, as common for more established techniques such as (scanning) transmission X-ray microscopy (STXM) or photo emission electron microscopy (PEEM), are not yet available.…”
Section: Introductionmentioning
confidence: 99%